Bearing Capacity of Sustainable Self-Compacting Concrete Walls - Mohammed, Akhlas H.; Al-saraj, Wissam; Zghair, Luma A. (Journal of Engineering and Sustainable Development, 2026)
The experimental program includes testing thirteen wall panels divided into five categories; every group comprises three specimens. The first group explains the aspect ratio (AR) effect with three values (0.5,0.625 and 0.75). The increase in AR results in a decrease in the ultimate load and an increase in the lateral displacement. In the second group, the slenderness ratio (λ) is investigated by the ratios (11.43, 13.33, and 16). The maximum load increases and the displacement decreases as it decreases. The third and fourth groups clarify the opening’s effect (dimensions and locations). The results indicated a decrease in failure load and displacement as the size of the opening increases and as it approaches the edges. So, the largest load and displacement were when the opening was 15x25 cm at the center. The last group had the same details as the first group’s samples, but these were tested in a two-way manner that caused a rise in the loading capacity by 15%.